An analysis of Learners’ Analytical Expositions - Katharina Rustipa (Dinamika Bahasa dan Budaya, 2008)
This article deals with learners’ Analytical Exposition Monologues. It is argued that the learners tend to bring to the target language the resources of their first language, whether or not those resources are actually available in the target language, resulting in failure to produce native-like speeches. This study therefore was conducted in order to find out the communicative purposes, the schematic structures, and the linguistic features that characterize the learners’ Analytical Exposition monologues using four students of FBIB University of Stikubank Semarang as the subjects of the study. It was found out that the communicative purposes, the schematic structures, and the linguistics features monologues match those produced by the English native speakers. However, the students make a number of lexicogrammatical errors which can be classified into tense errors, vocabulary errors, and finite errors. Based on the findings in this study, some suggestions are put forward, i.e. (1) the communicative purposes, the schematic structures, the linguistic features of genres in the target language should be taught to the students because they characterize certain genres; (2) the teachers and the students can learn from the errors they make in this study. More practice is thus required on the part of the students. Key words: thesis statement, argument, reorientation, linguistic features, lexicogrammar, communicative purpose, schematic structure, monologue, finite